Study on the potential mechanism of the active components in YiYiFuZi powder in homotherapy for hetropathy of coronary heart disease and rheumatoid arthritis - Wang, Yuming; Li, Xiaokai; Gu, Kun; Gou, Jing; Li, Xue; Dong, Yaqian; Li, Rui; Wei, Jinxia; Dou, Zhiying; Li, Yubo (Frontiers in Chemistry, 2022)
In recent years, the incidence of coronary heart disease and rheumatoid arthritis has been increasing, which has become a common public health problem worldwide. YiYiFuZi (YYFZ ) powder is a classical traditional Chinese prescription, which is commonly used to treat metabolic diseases such as rheumatoid arthritis, with an ideal curative effect, but the therapeutic mechanism is still unclear. In this study, from the perspective of clinical metabolomics, combined with network pharmacology, we sought the comorbidity mechanism and key targets of coronary heart disease and rheumatoid arthritis and the mechanism by which YYFZ powder exerts therapeutic effects, combined with molecular docking and atomic force microscopy to determine the effective components, and found that the higenamine and steroid components in YYFZ powder can bind acid sphingomyelinase enzymes to affect the sphingolipid pathway to produce therapeutic effects, which can bind to sugars existing as a glycoside.